State Planned Economy within the Modern Economic Regime - BORTNIKOV, Sergey P. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).04, 2018)
The author considers institute planning and its existence under the market relations. Protection of the capital requires support of its freedom, special nature of assignment and distribution of the benefits, determination of the rights of his owner opposed to the rights of employees. The role of the government, thus, comes down to capital servicing and its functions. In planned economy, on the contrary, the government sets rules, not the owner of the capital, but the person and the state becomes the central figure. The plan as the law defines conditions of managing, a customer of the public benefits. The possibility of existence of two-circuit system under which the government administration extends only to the enterprises with the government involvement is considered, private enterprises remain rather free. The plan is considered as the quantitative regulator and also as institutional and legal frameworks of the economy.